Efeito da modulação da via da esfingosina na resolução da resposta inflamatória induzida por lipopolissacarídeo (LPS) - Denise Alves Perez (2016)
Sphingosine, an important sphingolipid derived from plasma membrane, plays a fundamental role in many cellular processes including cell proliferation, angiogenesis, senescence and apoptosis. However its role to inflammation resolution remains unclear. Here, was proposed to evaluate the role of sphingosine pathway on neutrophil accumulation and survival in the pleural cavity of LPS-challenged mice and in isolated human neutrophils. For this purpose, mice received i.pl. administration of LPS (250 ng/cavity) or PBS. First, the expression of S1P receptors was evaluated in the cells of pleura or murine neutrophils stimulated with LPS, by qPCR and western blot. The next step we evaluated the effect of the treatments with sphingosine pathway modulators such as the L-Cycloserine, DL-threo-Dihydrosphingosine (DTD), CAY10621, CAY10444, FTY720 and JTE013 in the cells of pleura. Thus, the drugs are efficient in decreased the number of neutrophil and increased the percentage of apoptotic cells and phagocytosis of apoptotic cells (efferocytosis). Furthermore, we analysed the effect of S1P administration in pleural cavity to observed inflammatory activity. Human in vitro assay were performed to to study the drug’s effects in human apoptosis. We performed efferocytosis in vivo assay. The LPS stimuli increased the expression of S1PRs, in vitro and in vivo. The inhibition of S1P pathway and the treatment with the antagonists of receptors are efficient in decreased the cells in the pleural cavity, increased the neutrophils apoptosis and induced the efferocytosis in the inflamed tissue. The same effect was observed in vitro assay, increased of human apoptosis. The inhibition of S1P pathway and S1PRs showed a resolutive strategy.